Высшая математика. Дифференциальное и интегральное исчисление функции одной переменной - Арефьев К. П. Константин Петрович; Ефремова О. Н. Оксана Николаевна; Столярова Г. П. Галина Петровна; Глазырина Е. Д. Елена Дмитриевна (Томск, Изд-во ТПУ, 2011)
В фонде НТБ ТПУ отсутствует